Ochratoxin A production and amplified fragment length polymorphism analysis of Aspergillus carbonarius, Aspergillus tubingensis, and Aspergillus niger strains isolated from grapes in Italy - Perrone, Giancarlo; Mulè, Giuseppina; Susca, Antonia; Battilani, Paola; Pietri, Amedeo; Logrieco, Antonio (Applied and environmental microbiology, 2006)
Ochratoxin A is a potent nephrotoxin and a possible human carcinogen that can contaminate various agricultural products, including grapes and wine. The capabilities of species other than Aspergillus carbonarius within Aspergillus section Nigri to produce ochratoxin A from grapes are uncertain, since strain identification is based primarily on morphological traits. We used amplified fragment length polymorphisms (AFLPs) and genomic DNA sequences (rRNA, calmodulin, and beta-tubulin genes) to identify 77 black aspergilli isolated from grape berries collected in a 2-year survey in 16 vineyards throughout Italy. Four main clusters were distinguished, and they shared an AFLP similarity of <25%. Twenty-two of 23 strains of A. carbonarius produced ochratoxin A (6 to 7,500 microg/liter), 5 of 20 strains of A. tubingensis produced ochratoxin A (4 to 130 microg/liter), 3 of 15 strains of A. niger produced ochratoxin A (250 to 360 microg/liter), and none of the 19 strains of Aspergillus "uniseriate" produced ochratoxin A above the level of detection (4 microg/liter). These findings indicate that A. tubingensis is able to produce ochratoxin and that, together with A. carbonarius and A. niger, it may be responsible for the ochratoxin contamination of wine in Italy.